α-Mangostin-phytosomes as a plausible nano-vesicular approach for enhancing cytotoxic activity on SKOV-3 ovarian cancer cells - Abdulmohsin J. Alamoudi; Shaimaa M. Badr-Eldin; Osama A. A. Ahmed; Serag Eldin I. Elbehairi; Mohammad Y. Alfaifi; Hani Z. Asfour; Gamal A. Mohamed; Sabrin R. M. Ibrahim; Ashraf B. Abdel-Naim; Hossam M. Abdallah (SpringerOpen, 2024)
Abstract Background α-Mangostin is a major xanthone in Garcinia mangostana L. (Clusiaceae) pericarps. It has promising anti-proliferative potential in different cancer cells; however, it has poor oral bioavailability. Phytosomes are used as a novel nano-based drug delivery system. The aim of this research was to enhance the anti-proliferative potency of α-mangostin by formulating it as α-mangostin-phytosome (α-M-PTMs) and assessing its impact on SKOV-3 ovarian cancer cells in comparison to pure α-mangostin. Results The size and entrapment efficiency of the proposed formulation were optimized using Box-Behnken statistics. The optimized formula was characterized using transmission electron microscope. The binding of α-mangostin to phospholipids was confirmed using Fourier-transform infrared (FTIR) spectroscopy. The optimized α-mangostin-phytosomes formula exhibited enhanced anti-proliferative activity with reference to raw α-mangostin. This was further substantiated by assessing the cell cycle phases that indicated an accumulation of SKOV-3 cells in the sub-G1 phase. Annexin-V staining revealed enhanced apoptotic activity in α-mangostin-phytosome-treated cells. This was associated with upregulation of CASP3 (Caspase-3), BAX (BCL2 Associated X, Apoptosis Regulator) and TP53 as well as down-regulation of BCL2 mRNA (B-Cell Leukemia/Lymphoma 2). Moreover, our data indicated enhanced ROS (Reactive oxygen species) production, cytochrome-C release, and disturbed MMP (mitochondrial membrane potential). Conclusion Encapsulation of α-mangostin in a phytosome nano-formula enhances its anti-proliferative effects in SKOV-3 cells via, at least in part, inducing mitochondrial apoptotic cell death.